Surgical rehabilitation of patients with spinal neurotrophic decubitus - S. G. Shapovalov; E. P. Suhoparova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
The greatest weight neurodystrophic process develops in traumatic spinal cord injury, appears as neurotrophic decubitus (bedsores). There is a high risk of wound infection in the event of pressure ulcers. Surgical repair of the skin integrity in spinal patients of 3 and 4 grade is a basic prerequisite for the further complex of the rehabilitation measures. Work objective: to develop the concept of innovative technologies of treatment of local physical impacts and to implement it in surgical system of rehabilitation of patients with spinal cord lesion with neurotrophic decubitus of 3 and 4 grade. Clinical studies subjected 49 (100%) patients with spinal cord lesions and neurotrophic decubitus of 3 and 4 grade. All patients were divided into two groups: 1– (study group 1) 29 patients; 2 – (control group 2) 20 patients. The managed negative pressure system S042 NPWT VivanoTec (Hartmann), a method of ultrasonic cavitation (Sonoca%180), the system for the hydro surgery Versajet Smith and Nephew were used in the 1%st group. Traditional dressings for the preparation of a plastic closure of the wound defect neurotrophic decubitus of the grade 3%4 were used in the 2nd group. Statistical analysis was performed using package of Microsoft Excel%97 Statistica for Windows 6.0, SPSS 10.0 for Windows. The study showed that the use of complex methods of vacuum therapy, ultrasound cavitation and hydro surgical in the 1st group significantly reduces the duration of treatment compared with conservative methods in the 2nd group. In group 1, the mean duration of treatment was 19.9±13.9 days, in group 2 (comparison group) – 40.0±28.2 days (p<0.05). The usage of physical methods (managed negative pressure system, ultrasonic processing method, hydro surgical system) local treatment is a highly effective method of preparation neurotrophic decubitus grade 3 and 4 to the early recovery of the skin. Physical methods of local treatment have a positive effect on tissue regeneration and reduces periods of maturing granulation tissue. Axial flaps allow adequately perform the restoration of the skin in case of neurotrophic decubitus grade 3 and 4.